Postharvest Drying Techniques Regulate Secondary Metabolites and Anti-Neuroinflammatory Activities of Ganoderma lucidum - Sadiq, Nooruddin-bin; Ryu, Da-Hye; Cho, Jwa-Yeong; Lee, A-Hyeon; Song, Dae-Geun; Dorjsembe, Banzragch; Kim, Jin-Chul; Jung, Je-Hyeong; Nho, Chu-Won; Hamayun, Muhammad; Yang, Seung-Hoon; Kim, Ho-Youn (MDPI, 2021)
Ganoderma lucidum extract is a potent traditional remedy for curing various ailments. Drying is the most important postharvest step during the processing of Ganoderma lucidum. The drying process mainly involves heat (36 h at 60 degrees C) and freeze-drying (36 h at -80 degrees C). We investigated the effects of different postharvest drying protocols on the metabolites profiling of Ganoderma lucidum using GC-MS, followed by an investigation of the anti-neuroinflammatory potential in LPS-treated BV2 microglial cells. A total of 109 primary metabolites were detected from heat and freeze-dried samples. Primary metabolite profiling showed higher levels of amino acids (17.4%) and monosaccharides (8.8%) in the heat-dried extracts, whereas high levels of organic acids (64.1%) were present in the freeze-dried samples. The enzymatic activity, such as ATP-citrate synthase, pyruvate kinase, glyceraldehyde-3-phosphatase dehydrogenase, glutamine synthase, fructose-bisphosphate aldolase, and D-3-phosphoglycerate dehydrogenase, related to the reverse tricarboxylic acid cycle were significantly high in the heat-dried samples. We also observed a decreased phosphorylation level of the MAP kinase (Erk1/2, p38, and JNK) and NF-kappa B subunit p65 in the heat-dried samples of the BV2 microglia cells. The current study suggests that heat drying improves the production of ganoderic acids by the upregulation of TCA-related pathways, which, in turn, gives a significant reduction in the inflammatory response of LPS-induced BV2 cells. This may be attributed to the inhibition of NF-kappa B and MAP kinase signaling pathways in cells treated with heat-dried extracts.
Keywords: NF-KAPPA-B; INFLAMMATORY CYTOKINES; MICROGLIA; GLYOXYLATE; EXPRESSION; INVASION; PATHWAYS; FRACTION; CULTURE; CYCLES